Identification of Student Misconceptions Using A Three-Tier Test on The Concept of Atoms, Ions, and Molecules - Fanfiana, Rieke Oktavia; Hadisaputra, Saprizal; Supriadi (FKIP University of Mataram, 2024)
This research aims to identify misconceptions of the grade ninth students at MTs Al-Ishlahuddiny Putra Kediri Lombok using a three-tier test on the concept of atoms, ions, and molecules. This type of research is descriptive qualitative. The population in this study was class IX students at MTs Al-Ishlahuddiny Putra Kediri, consisting of 216 students. Sampling was carried out using a random sampling technique using the Slovin formula, and a sample of 68 students was obtained. The instrument used in this research is the three-tier test instrument by Riana Dewi Astari and has been validated using product moment correlation. The research results showed that the average percentage of students who experienced misconceptions was 23%, classified as low. Most students need clarification regarding the connection between the concept of compound molecules and elements and the concept of ions that release and receive electrons. Factors that cause misconceptions among students are the gap between preconceptions and concept assimilation, the objects being studied being abstract or difficult for students to understand, and the incompleteness of the information students receive during learning.